The challenge of a face-to-face meeting: when offenders meet their victims during mediation - Meléndez, Anna (Revista de victimología, 2021)
Meeting the other face-to-face can be a challenging experience for both, victim and offender. This article focuses on the analysis of the mediation process in order to evaluate three of the effectiveness indicators of restorative practices-, such meeting face to face, participation and communication between the parties. Quantitative and qualitative methodology have been used, consisting in non-participant observation of the face-to-face and indirect meetings (12)1; post-test questionnaires (40) completed by the offenders after mediation, and finally, a post-mediation interview (12) six months later. From the results, it was possible to acknowledge how they felt and what meeting their victims had meant for them, as well as it was possible to evaluate participation and communication between parties during and after their meeting. One of the aims was to find out whether offenders were able to understand the impact of the offence on the victims after having listened to them. Another aim was to identify a positive movement or mutual understanding between victims and offenders. Finally, another purpose was rating and analysing levels of participation and quality of communication. The outcomes can be globally seen as somewhat positive because almost half of the sample were able to understand their victims after having spoken with them.